2004
DOI: 10.1136/ard.2003.018440
|View full text |Cite
|
Sign up to set email alerts
|

Leflunomide inhibits transendothelial migration of peripheral blood mononuclear cells

Abstract: Objectives: To test whether the active metabolite of leflunomide (LEF-M), in addition to blocking the proliferation of activated lymphocytes by inhibiting dihydro-orotate dehydrogenase (DHODH), influences the transendothelial migration (TEM) of peripheral blood mononuclear cells (PBMC). Methods:In an in vitro model of PBMC transmigration through an endothelial cell (EC) barrier, PBMC were re-collected in three groups: cells not adherent to the EC, cells bound to, and cells which had migrated through, the EC la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 32 publications
2
16
0
3
Order By: Relevance
“…Also, inhibited activation of monocytic cells by A77 1726-treated T cells (34) may be related to altered integrin avidity. Our data showing a complex influence of teriflunomide on integrin function are consistent with recent data that show that this drug also interferes with leukocyte/endothelial interactions (35). This peculiar property, which is not shared by most other currently used immunosuppressive drugs, such as calcineurin inhibitors, might also be involved in the beneficial effects of malononitrilamides on chronic allograft rejection (5,36).…”
Section: Discussionsupporting
confidence: 80%
“…Also, inhibited activation of monocytic cells by A77 1726-treated T cells (34) may be related to altered integrin avidity. Our data showing a complex influence of teriflunomide on integrin function are consistent with recent data that show that this drug also interferes with leukocyte/endothelial interactions (35). This peculiar property, which is not shared by most other currently used immunosuppressive drugs, such as calcineurin inhibitors, might also be involved in the beneficial effects of malononitrilamides on chronic allograft rejection (5,36).…”
Section: Discussionsupporting
confidence: 80%
“…10 25 Lef-M was found to influence the transendothelial migration of PBMC by inhibiting DHODH in treated RA patients (mainly monocytes). 11 Fluorocytometric analysis of PBMC subsets within the migrated population showed a decrease in monocytes, but not in B or T cells, after Lef-M treatment. Furthermore, incubation with Lef-M of the PBMC from RA patients also decreased other cell adhesion molecule activity, such as monocytic CD44 expression and PBMC-hyaluronan binding.…”
Section: Discussionmentioning
confidence: 96%
“…[8][9][10] Recently, Lef-M was found to influence the transendothelial migration of peripheral blood mononuclear cells (PBMC) and to decrease cell adhesion molecule activity, such as monocytic CD44 expression and PBMC-hyaluronan binding by inhibiting DHODH in treated RA patients. 11 All these effects might act together to block cell activation and cell traffic into inflamed RA synovial tissue.…”
mentioning
confidence: 99%
“…Cutolo et al could demonstrate that the active metabolite of leflunomide, A771726, showed anti-inflammatory effects on LPS activated cultured macrophages derived from RA patients [21]. Grisar et al reported that only a high concentration of 100 µM A771726 inhibited the transendothelial migration of inflammatory cells by reducing adhesion and transmigratory capacity [22].…”
Section: Discussionmentioning
confidence: 99%